1986
DOI: 10.1128/aem.52.4.892-897.1986
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of ornithine and arginine as specific precursors of clavulanic acid

Abstract: Ornithine and arginine (5 to 20 mM), but not glutamic acid or proline, exerted a concentration-dependent stimulatory effect on the biosynthesis of clavulanic acid in both resting-cell cultures and long-term fermentations of Streptomyces clavuligerus. Ornithine strongly inhibited cephamycin biosynthesis in the same strain. [1-14C]-, [5-14C]-, or [U-14 C] ornithine was efficiently incorporated into clavulanic acid, whereas the incorporation of uniformly labeled glutamic acid was very poor. [U-14C] citrulline wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 19 publications
2
25
0
4
Order By: Relevance
“…Indeed, ammonium interfered with arginine utilization, and at least two enzymes involved in the catabolism of this amino acid are regulatory targets. Arginase activity has been reported in S. clavuligerus and found to be induced by arginine (Romero et al, 1986). Our results confirmed this observation and also indicated that nitrogen control participates in arginase regulation, as described in other micro-organisms (Baumberg & Harwood, 1979;Broman et al, 1978).…”
Section: Bascaran C H a R D I S S O N A N D A F B R A~asupporting
confidence: 92%
“…Indeed, ammonium interfered with arginine utilization, and at least two enzymes involved in the catabolism of this amino acid are regulatory targets. Arginase activity has been reported in S. clavuligerus and found to be induced by arginine (Romero et al, 1986). Our results confirmed this observation and also indicated that nitrogen control participates in arginase regulation, as described in other micro-organisms (Baumberg & Harwood, 1979;Broman et al, 1978).…”
Section: Bascaran C H a R D I S S O N A N D A F B R A~asupporting
confidence: 92%
“…A 93.5% match was obtained, which indicates that the S. clavuligerus model predicts the activity of the diverse pathways for catabolism of the different carbon and nitrogen sources. These results are in good agreement with experimental reports [29][30][31].…”
Section: In Silico Prediction Of Carbon and Nitrogen Utilizationsupporting
confidence: 93%
“…S. clavuligerus produces several ,-lactam antibiotics, including clavulanic acid, a potent 1-lactamase inhibitor, and cephamycin C (13,24). Many studies have been carried out on the biosynthesis of cephamycins (2,8,26) and clavulanic acid (26,27) and the control of antibiotic biosynthesis by this strain, which is becoming a model microorganism for the study of cephamycin biosynthesis. The development of recombinant DNA technology in S. clavuligerus is of great interest but has been hampered by the difficulty in regenerating cells from protoplasts and by the unavailability of suitable cloning vectors and transformation systems.…”
mentioning
confidence: 99%